PEMEROLEHAN BAHASA KEDUA PADA ANAK USIA SD MELALUI KEGIATAN MENONTON SERIAL UPIN IPIN DI TELEVISI - MARWANI MARWANI (Universitas Islam Malang, 2022)
Language Aquisition or commonly referred to as language acquisition is very important in human life. Language is a means of communication when interacting with others, which must be mastered by humans from an early age. Language acquisition and good language mastery mastered from an early age can support the quality of human life, especially in the aspect of social interaction with others. Therefore, given the importance of early language acquisition, language acquisition in children is important to learn. This article will present some brief reviews of language acquisition in terms of design and how language acquisition in children is obtained through electronic media, namely by watching the Upin Ipin animated series on television. The source of data in this study is the